The use of argon cluster bombardment for the surface preparation of paint cross‐sections for analysis by ToF‐SIMS1. (22nd May 2014) - Vermeulen, M.; Poleunis, C.; Delcorte, A.; Bertrand, P.; Sanyova, J.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Surface preparation with gas cluster ion beam (GCIB) sputtering was performed on paint cross‐sections, which belong to the collection of the Royal Institute for Cultural Heritage (KIKIRPA), Brussels, Belgium. Superficial cleaning of cross sections with residual embedding resin surface contamination was studied with different sputtering times in order to obtain a gain in the spectral and imaging mode. Sputtering was made directly through the Time‐of‐Flight‐SIMS apparatus. It was thus demonstrated that GCIB sputtering for a short period was very efficient for the superficial decontamination of cultural heritage cross‐sections without visible damage on the valuable samples. The GCIB sputtering time and dose can be highly decreased when combined with a monoatomic argon ion beam preparation techniques such as the ion milling systems. Copyright © 2014 John Wiley & Sons, Ltd.